Radioactive iodine (RAI) therapy for metastatic differentiated thyroid cancer. Issue 3 (June 2017) - Verburg, Frederik A.; Hänscheid, Heribert; Luster, Markus
Abstract : Differentiated thyroid cancer (DTC) is the most common endocrine malignancy. It usually has a comparatively benign course. If properly executed, radioiodine therapy can provide an effective treatment of even advanced, metastatic DTC. A major problem in determining the right RAI for a patient with metastatic disease is a comparative lack of evidence. There are no reports on randomized controlled trials in this patient group which can aid us in determining which way to treat which patient. Few non-randomized prospective observational studies have been performed. Most available evidence is based on retrospective analyses which, although often informative, still are hampered by the selection bias inherent to retrospective studies on a small, preselected sample of the total DTC population. The aim of the present review is to provide an overview of the relevant literature on the issues pertinent to the execution of RAI. Radioiodine therapy of metastatic DTC in patients can be an effective treatment modality which will contribute significantly to a patients' life expectancy. However, much is unclear in the management of this malignancy, including which activity to use, how to determine this activity (empiric vs. dosimetric approach) as well as the potential long-term complications. In pediatric patients, special considerations apply with regard to weight-adaptation of activities as well the risk of pulmonary fibrosis in patients with diffuse miliary metastases.